Descemet membrane endothelial keratoplasty (DMEK): clinical results of precut versus surgeon-cut grafts - Koechel, Doreen (Graefes Arch Clin Exp Ophthalmol, 2020)
PURPOSE: This study aims to investigate possible differences in clinical outcomes between precut and surgeon-cut grafts for Descemet membrane endothelial keratoplasty (DMEK). METHODS: 142 consecutive patients who underwent DMEK were included in the study. 44 patients received precut tissues, and 98 patients received surgeon-cut tissues. Precut grafts were allocated to the patient by the German Society for Tissue Transplantation if available. We compared the outcomes of both groups for changes in visual acuity, central corneal thickness, endothelial cell density, re-bubbling rate, and graft failure rate. RESULTS: Patients who received precut tissues experienced similar increase in visual acuity (median change 0.4 logMAR) and decrease of corneal swelling (median change 132 μm) compared with those who received surgeon-cut tissues (median VA change 0.3 logMAR, p = 0.55, CCT change 118 μm, p = 0.63). There was no statistical difference in endothelial cell density (1436 vs. 1569 cells/mm(2), p = 0.37), re-bubbling (32% vs. 35%, p = 0.85), and graft failure rate (5% vs. 1%, p = 0.23). No primary graft failure occurred in the group of precut grafts. CONCLUSION: Both methods lead to comparable results for visual acuity, corneal deswelling, endothelial cell density, and re-bubbling rate. A previously described higher graft failure rate for precut tissues could not be confirmed in our study. Thus, we do not see medical reasons against the use of precut tissues. There are several advantages of precut DMEK tissues over surgeon-cut tissues, especially the prevention of graft loss during preparation in the operating theater.